Browning automatic rifle : from the 1918 to the 1918A3-SLR - Conroy, Bob, 1977-; Ruffin, Paul (Texas Review Press, 2015)
This book traces the evolution of the Browning Automatic Rifle from the Model of 1918, first to face combat in World War I, through its various configurations in all arenas of combat all the way to the present-day1918 A3 SLR developed and manufactured by Ohio Ordnance Works. The Browning Automatic Rifle, known simply as the BAR, was a shoulder-fired light machine gun fed by a twenty-round box magazine of 30-06, the same ammunition used by the 1903 Springfield. Weighing in at under twenty pounds, it could easily be carried by one soldier, who could drape a bandolier with twelve magazines over hi.